COVID-19 patients on hemodialysis: a hospital experience - Ribeiro,Bárbara (2020)
Introduction: SARS-CoV2 represents a challenge for hemodialysis (HD). By August 24 2020, the disease had affected 55720 people in Portugal. The northern Minho province has had 4428 cases. The Minho has 870 HD patients among 11 ambulatory HD centers and the Nephrology Department of Braga Hospital. Braga Hospital centralized HD treatments of COVID-19 patients. We describe our experience managing these patients. Results: We used a 2-station room and dedicated nurse with PPE but, as numbers increased, HD was performed in the main HD room. Disinfection protocols and specific routes were created. Swabs were repeated 14 days after diagnosis and then weekly until recovery. A total of 17 HD COVID-19 patients were diagnosed in the Minho, 16 of which performed HD in Braga Hospital. The first patient was diagnosed on March 16 and the last on May 5. Ten were males, mean age 60.6±13.2 years and median dialysis vintage 38.5 months (IQR 23.5-85.8). Four patients were diabetic and 10 were hypertensive. Only 1 of the 5 hospitalized patients was admitted for symptoms attributable to COVID-19. One developed severe respiratory insufficiency; 3 took hydroxychloroquine and 1 died. The 11 patients on ambulatory care had mild or no symptoms. At diagnosis, the mean hemoglobin was 10.1±1.8g/dL; mean leukocytes count 6.5±3.4x10/μL; mean platelet count 161±7x10/μL and mean LDH 241±148U/L. Median C reactive protein was 11.3mg/L (IQR 1.6-23.8). Patients swabs turned negative after a mean of 22±10 days. No association was found between the duration of a positive swab and gender, diabetes or hypertension. Discussion: Compared with the general population, Minho HD patients had a higher incidence of cases, possibly due to an increased risk and more testing. Incidence and mortality were lower than in other series. Centralizing infected patients may help prevent the spread of the disease and reduce the burden on HD centers.